Phil, Neil, the Production of Nature and me. Issue 1 (March 2023) - O'Keefe, Paul
The production of nature remains as a profoundly powerful framing of human–environment relations in capitalist society. It's relevance is evidenced when thinking of vulnerability to natural hazards, adaptation to climate change, Anthropocene versus capitalocene debates, and the linkages between and beyond these. It forces us to confront the politician-economic-ecological issues of who gets to produce and reproduce nature, what drives this change, and for what ends.